AB0249 Identification of inflammatory- and immune disorder- related proteins as putative biomarker candidates for improving rheumatoid arthritis monitoring. (15th June 2017) - González-Rodríguez, L; Calamia, V; Lourido, L; Fernández-Puente, P; Camacho-Encina, M; Ruiz-Romero, C; Julià, A; Fernández-Nebro, A; Tornero, J; Marsal, S; Blanco, FJ
Abstract : Background: Rheumatoid arthritis (RA) is a long-lasting inflammatory autoimmune disorder that ultimately leads to the destruction of joint architecture. Objectives: Using the DAS28 activity index, 80 RA serum samples (40 with low activity and 40 with high activity) were selected in order to be analyzed by mass spectrometry. The aim of this study was to find possible protein biomarkers that could discriminate patients with different RA activity in the daily clinical routine. Methods: In order to facilitate the complex measurement of these serum samples, a simple, fast and reproducible albumin-specific depletion method using ethanol was optimized and applied to this study. Four independent pools of the 40 high RA activity samples (10 samples per pool) and 4 pools of the 40 low RA activity samples were firstly albumin-depleted, and then the remnant serum proteins were digested and differentially labelled with iTRAQ 8-plex reagents. Subsequently, the 8 labelled pools were combined and cleaned using StageTips-C18. Finally, the pool mixture was fractionated by HPLC (Zorbax-C18) and the resulting fractions were analyzed by nanoLC-MS/MS using two different equipments for validation (MALDI-TOF/TOF and TripleTOF). Results: The mass spectrometry analysis led to the identification of 186 proteins. Among these, Haptoglobin, Kininogen-1, Alpha-2-HS-glycoprotein, Serum Amyloid A, Afamin and Histidine-rich-glycoprotein, exhibited a differential relative abundance depending on the RA activity of the patients (p<0.03) in both analysis. These proteins were also validated by other orthogonal techniques (western blot, ELISA and protein arrays). Conclusions: In this proteomic study, 9 proteins were found to be modulated between patients with high and low RA activity. Most of these proteins are related with the RA process and the effects caused by this type of disease (inflammation and immune disorder in joints). Therefore, these proteins are possible biomarker candidates for improving RA monitoring. Future validation experiments and prospective studies are needed to facilitate their implementation in the clinical routine. Disclosure of Interest: None declared